Management accounting practices in the Portuguese lodging industry - Santos, Luís Lima (2010)
Nowadays the increase in competition within the hotel and lodging industry is becoming more notorious, thus making more relevant the decision making process for managers, concerning the effective use of accounting tools to provide the necessary framework of information for their decisions. This study has the purpose of characterizing management accounting techniques in Portugal, identifying the traditional and contemporary techniques, the use of USALI, if the decision makers are satisfied with the information available, and determine which factors influence the industry to adopt a certain technique.